Transcardiac tunneling technique for endoscopic submucosal dissection of gastric fundus tumors arising from the muscularis propria - Lu, Jiaoyang; Zheng, Minhua; Jiao, Taotao; Wang, Yanan; Lu, Xuefeng (Endoscopy, 2014)
The promising endoscopic resection techniques for upper gastrointestinal submucosal tumors (SMTs) are challenged when performed in the gastric fundus. Here, we report on the development of a transcardiac endoscopic tunneling technique (TCTT) for the resection of tumors in this area. A total of 18 patients with gastric fundus SMTs arising from the muscularis propria on endoscopic ultrasound underwent TCTT. The procedure involved the excavation of a submucosal tunnel from the esophagus, through the cardia, to the gastric SMT for resection. The tunnel was closed by clips after retrieval of the tumor. The mean tumor size was 2.1 cm (range 0.8 – 5.0 cm). The mean procedure time was 75.1 minutes (range 40 – 100 minutes). Complete resection was achieved in all cases. Iatrogenic perforation occurred in one case. This and one other patient developed mild pneumoperitoneum on the day after the procedure; symptoms resolved under conservative management. No patient developed gastrointestinal leakage, delayed bleeding, or secondary infection. Therefore, in this pilot study, TCTT provided a definitive histological diagnosis as well as a feasible, safe, and easy therapeutic approach for gastric fundus SMTs arising from muscularis propria in the circular area within 8 cm below the cardia.